PENINGKATAN HASIL BELAJAR IPA MATERI CUACA DAN PENGARUHNYA BAGI MANUSIA DENGAN MENGGUNAKAN MEDIA VISUAL PADA SISWA KELAS III A DI SDN 004 PINANG SERIBU - Nurul Hikmah; Euis Kusumarini (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
This research is a Classroom Action Research aimed to improve science learning through visual media in grade 3 students A SDN 004 Pinang Seribu. This research was conducted in SDN 004 Pinang Seribu with research subjects of Class III A students, amounting to 30 students, consisting of 18 male students and 12 female students and the object of research is visual media. The study was conducted in three cycles. Cycle I held three meetings. Cycle II was held three meetings and cycle III was held three times, where every third meeting cycle was conducted evaluation test in the form of problem. Problem evaluation test learning each cycle shaped stuffing. Data were collected with documentation, end-cycle tests, and observations. The results showed that the activity of teachers and students as a whole is considered sufficient, whereas in cycle II, the activities of teachers and students as a whole experienced changes and improvements to be good. Where at the beginning before the cycle obtained an average score of 49.6, in the first cycle the average value that can reach 54.5 students, in cycle II the average value of 68.3 and the average third cycle that can be achieved 83, 6. Based on the research results can be concluded that visual media can improve the learning outcomes of science in grade III students A Pinang Seribu.Keywords: Learning Outcomes, Weather and Its Influence for Humans, Visual Media